2022
DOI: 10.3389/fcell.2022.1037149
|View full text |Cite
|
Sign up to set email alerts
|

A long non-coding RNA with important roles in the carcinogenesis

Abstract: Long non-coding RNAs are demonstrated to contribute to carcinogenesis. TMPO Antisense RNA 1 (TMPO-AS1) is an example of lncRNAs with crucial roles in this process. This lncRNA serves as a sponge for miR-320a, miR-383-5p, miR-329-3p, miR-126, miR-329, miR‐199a‐5p, miR-577, miR-4731-5p, miR-140-5p, miR-1179, miR-143-3p, miR-326, miR-383-5p, let-7c-5p, let-7g-5p, miR-199a-5p, miR-200c, miR-204-3p, miR-126-5p, miR-383-5p, miR-498, miR-143-3p, miR-98-5p, miR-140 and miR-143. It can also affect activity of PI3K/Akt/… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 49 publications
0
4
0
Order By: Relevance
“…With the development of second-generation sequencing technology, researchers have proved that lncRNAs play an essential role in many biological fields such as tumor development, neuroscience and individual development, and are important regulatory molecules of the human genome. Among the many functions of lncRNAs, the main ones related to tumors are maintaining cell growth and proliferation, promoting metastasis and invasion, inducing angiogenesis and inhibiting apoptosis [ 89 , 90 ]. It has been found that lncRNAs are dysregulated and aberrantly expressed in a number of tumors [ 91 ].…”
Section: Liquid Biopsy and The Main Detection Objectsmentioning
confidence: 99%
“…With the development of second-generation sequencing technology, researchers have proved that lncRNAs play an essential role in many biological fields such as tumor development, neuroscience and individual development, and are important regulatory molecules of the human genome. Among the many functions of lncRNAs, the main ones related to tumors are maintaining cell growth and proliferation, promoting metastasis and invasion, inducing angiogenesis and inhibiting apoptosis [ 89 , 90 ]. It has been found that lncRNAs are dysregulated and aberrantly expressed in a number of tumors [ 91 ].…”
Section: Liquid Biopsy and The Main Detection Objectsmentioning
confidence: 99%
“…The article also states that Elevated expression of TMPO-AS1 is linked to an unfavorable prognosis in patients with lung adenocarcinoma (LUAD). 8688…”
Section: Introductionmentioning
confidence: 99%
“…The article also states that Elevated expression of TMPO-AS1 is linked to an unfavorable prognosis in patients with lung adenocarcinoma (LUAD). [86][87][88] Ren's article on Cancer Cell International that discusses the function of LINC01116 in lung adenocarcinoma (LUAD). LINC01116, a lengthy noncoding RNA induced by EGR1, promotes the oncogenic characteristics of LUAD by interacting with the miR-744-5p/CDCA4 axis.…”
Section: Introductionmentioning
confidence: 99%
“…LncRNA expression is restricted to low copy numbers in different cells at specific developmental stages [16]. LncRNAs either act as ceRNA molecular sponges for miRNAs or serve as functional scaffolds that recruit regulatory proteins to their target chromosomal regions [17,18].…”
Section: Introductionmentioning
confidence: 99%